The Changes of United States Foreign Policy in The Arctic in 2022 - Sella, Nofra (CV. AFDIFAL MAJU BERKAH, 2024)
The United States' (U.S.) attention to the Arctic region has intensified in recent years due to the opening of vast natural resources and the potential for new shipping routes resulting from global warming. As an Arctic nation, the U.S. has actively focused on the region. From its initial Arctic policy in 1971 until 2021, U.S. foreign policy remained relatively passive, merely outlining the general U.S. position in the region. However, in 2022, without significant changes or upheavals in the Arctic region, the U.S. significantly altered its foreign policy by incorporating military instruments To explore that factors that influenced the change in U.S. policy in the Arctic in 2022, this study employs the decision-making process theory. Utilizing qualitative research methods, the study relies on both primary and secondary data, drawn from official U.S. policies, supplemented by credible articles, news, and scholarly writings. The research identifies three factors that led to the U.S. altering its foreign policy in the Arctic in 2022: domestic political conditions, economic and military factors, and the international context.